2020
DOI: 10.1093/jtm/taaa061
|View full text |Cite
|
Sign up to set email alerts
|

Zika among international travellers presenting to GeoSentinel sites, 2012–2019: implications for clinical practice

Abstract: Introduction International travellers contribute to the rapid spread of Zika virus (ZIKV) and its sentinel identification globally. We describe ZIKV infections among international travellers seen at GeoSentinel sites with a focus on ZIKV acquired in the Americas and the Caribbean, describe countries of exposure and traveller characteristics, and assess ZIKV diagnostic testing by site. Methods Records with an international tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A study predicted that a large portion of tropical and subtropical regions globally have suitable environmental conditions with over 2.17 billion people inhabiting these areas [41], raised concerns about the high risk of introducing and establishing new autochthonous transmission in these areas [4]. These travel-related ZIKV infections can be reduced by the following: a) travellers should discuss their travel plans with their healthcare providers to ensure that prevention measures are taken [42,43]; b) ZIKV infection should remain a consideration for travellers returning from the ZIKV outbreak area [42]; and c) avoidance of the primarily daytime-biting Aedes mosquitos both during and after travel [43].…”
Section: Discussionmentioning
confidence: 99%
“…A study predicted that a large portion of tropical and subtropical regions globally have suitable environmental conditions with over 2.17 billion people inhabiting these areas [41], raised concerns about the high risk of introducing and establishing new autochthonous transmission in these areas [4]. These travel-related ZIKV infections can be reduced by the following: a) travellers should discuss their travel plans with their healthcare providers to ensure that prevention measures are taken [42,43]; b) ZIKV infection should remain a consideration for travellers returning from the ZIKV outbreak area [42]; and c) avoidance of the primarily daytime-biting Aedes mosquitos both during and after travel [43].…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 Although Zika virus has disappeared as a public health problem, sporadic cases still occur in the Americas and in travellers. 51 , 52 …”
Section: Public Health Emergency Of International Concern (Pheic)mentioning
confidence: 99%
“…A literature review of the GeoSentinel publications related to Zika showed that Zika was first reported by GeoSentinel already in 2012, and notifications peaked in the years 2016–17 reflecting the public health emergency in the Americas at the time [ 86 ]. GeoSentinel sites reported 525 ZIKV cases from 2012 through 2019 with a clear decline in travellers after the 2016 outbreak [ 87 ]. Main countries of exposure were the Caribbean Islands and Latin America.…”
Section: E Zikaplan’s Research On Zika’s Geographic Spread Via Intern...mentioning
confidence: 99%